Principles of Marketing - Maria Gomez Albrecht; Mark C. Green; Linda Hoffman (OpenStax, 2023)
Principles of Marketing is designed to meet the scope and sequence for a one-semester marketing course for undergraduate business majors and minors. Principles of Marketing provides a solid grounding in the core concepts and frameworks of marketing theory and analysis so that business students interested in a major or minor in marketing will also be prepared for more rigorous, upper-level elective courses. Concepts are further reinforced through detailed, diverse, and realistic company and organization scenarios and examples from various industries and geographical locations. To illuminate the meaningful applications and implications of marketing ideas, the book incorporates a modern approach providing connections between topics, solutions, and real-world problems. Principles of Marketing is modular, allowing flexibility for courses with varied learning outcomes and coverage.
Keywords: 650; Marketing; Marketing